HUBUNGAN ANTARA FAKTOR MANAJEMAN DAN SARANA PRASARANA DENGAN PELAYANAN KESEHATAN PADA MASA PANDEMI COVID-19 DI PUSKESMAS PANIKI BAWAH KOTA MANADO - Amiman, Anjani Hartina (ARCHIVE OF COMMUNITY HEALTH, 2023)
The Covid-19 pandemic that we are currently facing has brought about major changes, because we are required to take preventive measures to reduce the risk of spreading Covid-19. The health aspect is also included in the impact, such as in providing services carried out by every health facility including the Puskesmas. The management of the puskesmas is managed to remain effective and efficient in providing services, which is supported by the facilities and infrastructure facilities at the puskesmas. The aim of this research is to examine the relationship between management factors and infrastructure and health services during the Covid-19 pandemic. This is a cross-sectional study design study that was conducted in May 2022 at the Paniki Bawah Health Center, in May 2022 as many as 70 respondents were taken using a purposive sampling technique, and analyzed using the Fisher`s Exact Test. The results showed that the management factor with healthcare had a ? value of 0.000 so that the value of ? <0.05 and infrastructure facilities with healthcare had a ? value of 0.000 so that the value of ? <0.05. The conclusion of this study is that there is a link between management factors and health facilities and services during the Covid-19 pandemic. Keywords: Health Center Management, Infrastructure, Health Services